Spontaneous formation and relaxation of spin domains in antiferromagnetic spin-1 condensates - K. Jiménez-García (Nature Portfolio, 2019)
Order parameter and phase characterization of multicomponent quantum system is of fundamental importance. Here the authors show the parameter control of the dynamics and relaxation of the magnetic ordering of the spin-1 Bose-Einstein condensates of sodium atoms in uniform magnetic field.